The Effect of Religious Music Therapy on Reducing Menstrual Pain Among Midwifery Students: A Non-Pharmacological Approach - Rizki, Lailatul Khusnul; Kartika Sari, Feby; Anggraini, Fritria Dwi; Abidah, Siska Nurul (Jurnal Ilmiah Kesehatan, 2025)
Primary dysmenorrhea is a common menstrual disorder affecting women of reproductive age, particularly adolescents and young adults. Many students experience menstrual pain, potentially interfering with academic and daily activities. This study investigates the effectiveness of religious music therapy in reducing the intensity of primary dysmenorrhea among undergraduate midwifery students at Universitas Nahdlatul Ulama Surabaya. This research used a pre-experimental design with a one-group pretest-posttest approach. The population was all third-semester undergraduate midwifery students who experienced primary dysmenorrhea. The sample consisted of 33 students, selected through purposive sampling. The intervention was a 30-minute religious music therapy session conducted during the first or second day of menstruation. The intensity of primary dysmenorrhea was measured using the Numeric Rating Scale (NRS). Data analysis used the Wilcoxon Signed-Rank Test with a significance level of α = 0.05. Before the intervention, most participants experienced moderate menstrual pain (63.6%), while a few reported mild (30.3%) and severe (6.1%). After the intervention, most respondents reported mild menstrual pain (78.8%), and a few had moderate (21.2%). The Wilcoxon test result obtained p=0.000, showing a statistically significant reduction in menstrual pain after the religious music intervention. Religious music therapy effectively reduces the intensity of primary dysmenorrhea. It is potentially a non-pharmacological therapy to manage menstrual pain.